Hexachlorobenzene as a differential modulator of the conventional and metronomic chemotherapy response in triple negative breast cancer cells - Sanchez, Yamila (2024)
Aim: Triple negative breast cancer (TNBC) is usually treated with high doses of paclitaxel, whose effectiveness may be modulated by the action of environmental contaminants such as hexachlorobenzene. High doses of paclitaxel cause adverse effects such as low cellular selectivity and the generation of resistance to treatment due to an increase in the expression of multidrug resistance proteins. These effects can be reduced using a metronomic administration scheme with low doses. This study aimed to investigate whether hexachlorobenzene modulates the response of cells to conventional chemotherapy with paclitaxel or metronomic chemotherapy with paclitaxel plus carbachol, as well as to study the participation of the MRP ATP-binding cassette transporter G2 (ABCG2) in human TNBC MDA-MB231 cells.Methods: Cells were treated with hexachlorobenzene alone or in combination with conventional or metronomic chemotherapies. The effects of treatments on cell viability were determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and the nuclear factor kappa B pathway participation was evaluated using a selective inhibitor. ABCG2 expression and its modulation were determined by Western blot.Results: Results confirmed that paclitaxel reduces MDA-MB231 cell viability in a concentration-dependent manner. Results also showed that both conventional and metronomic chemotherapies reduced cell viability with similar efficacy. Although hexachlorobenzene did not modify cell viability per se, it did reverse the effect induced by the conventional chemotherapy, without affecting the efficacy of the metronomic chemotherapy. Additionally, a differential modulation of ABCG2 expression was determined, mediated by the nuclear factor kappa B pathway, which was directly related to the modulation of cell sensitivity to another cycle of paclitaxel treatment.Conclusions: The findings indicate that, in human TNBC MDA-MB231 cells, in the presence of hexachlorobenzene, the metronomic combination of paclitaxel plus carbachol is more effective in affecting the tumor biology than the conventional therapeutic administration scheme of paclitaxel.